A direct charger transfer from interface to surface for the highly efficient spatial separation of electrons and holes: The construction of Ti–C bonded interfaces in TiO2-C composite as a touchstone for photocatalytic water splitting. (March 2017) - Yang, Yurong; Gao, Peng; Wang, Ying; Sha, Linna; Ren, Xiaochen; Zhang, Jianjiao; Chen, Yujin; Wu, Tingting; Yang, Piaoping; Li, Xiaobo
Abstract: The construction of semiconductor composites is known a powerful method to realize the spatial separation of electrons and holes, which results in more electrons or holes dispersing on the surface, accompanying a charge transfer and further extending the region of charge depletion at the interface between these two components of the composite. However, most of them are based on a random accumulation connection of two different crystals and there are obvious empty spaces, which are formed as deplete layer to hinders the charge transfer to a large extent. In order to shorten the charger transfer path and make a direct charge transform from interface to surface, a chemically bonded interface in the composite is more reasonable. In this work, using one-dimensional TiO2 -C composite nanorods with a Ti–C chemically bonded interface as a touchstone, which was prepared through a simple carbonized process, the above strategy for better semiconductor photocatalytic water splitting property has been realized. Graphical abstract: TiO2 -C composite with a Ti–C chemically bonded interface can short the charger transfer path and make a direct charger transform from interface to surface. TiO2 -C composite displayed exceptional photoelectron responses compared to TiO2 /C composite without Ti–C bond. The rate of visible-light driven photocatalytic water splitting for H2 generation of TiO2 -C was about 12 times of TiO2 /C composite. Highlights: TiO2 -C composite with a Ti–C chemically bonded interface short the charger transfer path. TiO2 -C composite displayed exceptional photoelectron responses compared to TiO2 /C composite without Ti–C bond. The rate of visible-light driven photocatalytic water splitting for H2 generation of TiO2 -C was about 12 times of TiO2 /C composite.